Perspectives of vaccination in Chagas disease revisited - Erney Plessmann Camargo (Memorias do Instituto Oswaldo Cruz, 2009)
The perspectives for a Chagas Disease vaccine 30 years ago and today are compared. Antigens and adjuvants have improved, but logistic problems remain the same. Sterilizing vaccines have not been produced and animal models for chronic Chagas have not been developed. Vector control has been successful and Chagas incidence has come to a halt. We do not have a population candidate to vaccination now in Brazil. And if we had, we would not know how to evaluate the success of vaccination in a short time period. A vaccine may not seem important at the moment. However, scientific reasons and incertitudes about the future recommend that a search for a vaccine be continued.